Silicon dioxide micropowder for aluminum-based copper-clad plate as well as preparation method and application of silicon dioxide micropowder
By ball milling, grading and surface modification of silicon powder in aluminum-based copper clad plate, the problem of insufficient dispersion and bending strength of existing fillers in aluminum substrates is solved, and efficient thermal conductivity and low-cost aluminum substrate preparation are achieved. .
Patent Information
- Application Number
- CN202411419404.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-11
- Publication Date
- 2025-01-10
AI Technical Summary
When used in aluminum substrates, existing high thermal conductivity fillers have problems such as low filler content, high cost, poor dispersion and low bending strength. In particular, dispersion and bending strength are the main obstacles to their application.
By ball milling and grading the silicon-containing raw materials, silicon powder with different particle sizes was obtained, and mixed with silane coupling agent for surface modification and compounding, obtain silica powder for aluminum-based copper clad plates, using optimized particle diameter Proportional and modification conditions to improve its dispersion and bending strength.
The high dispersion and high bending strength of silica fine powder in aluminum-based copper clad plate are achieved, which reduces production costs and improves thermal conductivity, interlayer adhesion, peel strength and other properties.
Smart Images

Figure CN119284912A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic non-metallic material processing and application, and in particular to silicon dioxide powder for aluminum-based copper-clad plates and a preparation method and application thereof. Background Art
[0002] Aluminum-based copper-clad laminate is a common metal substrate, which generally needs to have good thermal conductivity and electrical insulation performance. Its three main components are the circuit layer (generally electrolytic copper foil), the insulation layer and the metal base layer (aluminum). The insulation layer is the most critical technology of the aluminum substrate, which mainly plays the role of bonding, insulation and heat conduction. The insulation layer is the largest thermal barrier in the entire substrate structure. The lower the thermal resistance of the insulation layer, the more conducive it is to the diffusion of heat generated by the device during operation, and the more conducive it is to reduce the operating temperature of the device, thereby achieving the purpose of increasing the power load of the substrate, reducing the volume of the substrate, extending the service life, and increasing power output.
[0003] At present, high thermal conductivity fillers on the market include aluminum oxide, aluminum nitride, magnesium oxide, etc. However, when these high thermal conductivity fillers are used in aluminum substrates, there are problems such as low filler content, high cost, poor dispersibility and low bending strength. In particular, dispersibility and bending strength are the main obstacles restricting the application of this type of filler. Summary of the invention
[0004] The object of the present invention is to provide a silicon dioxide powder for aluminum-based copper-clad laminates and a preparation method and application thereof. The silicon dioxide powder for aluminum-based copper-clad laminates has both high dispersibility and high bending strength.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing silicon dioxide powder for aluminum-based copper-clad laminates, comprising the following steps:
[0007] The silicon-containing raw materials were ball-milled and classified in sequence to obtain particle sizes D 50 Silicon micropowders of different particle sizes are 2.5-3 μm, 5-6 μm and 9-10 μm respectively; the silicon-containing raw material is coarse silicon micropowder or quartz sand;
[0008] The silicon micropowders of different particle sizes are respectively mixed with silane coupling agents for surface modification, and the modified silicon micropowders of different particle sizes are mixed and compounded and then sieved to obtain silicon dioxide micropowder for aluminum-based copper-clad laminates;
[0009] The compounding mass ratio of the modified silicon micropowders with different particle sizes is (2.5-3 μm):(5-6 μm):(9-10 μm)=(10-15):(25-30):(50-60).
[0010] Preferably, the parameters of the crude silicon micropowder or quartz sand are independently whiteness ≥ 90%, magnetic impurity content ≤ 20 ppm, and purity ≥ 99.2%.
[0011] Preferably, the silane coupling agent includes one or more of epoxyalkoxysilane, aminoalkoxysilane and isocyanatealkoxysilane.
[0012] Preferably, the epoxyalkylalkoxysilane is 3-(2,3-epoxypropoxy)propyltrimethoxysilane, the aminoalkoxysilane is 3-aminopropyltrimethoxysilane; and the isocyanatealkoxysilane is 3-isocyanatepropyltrimethoxysilane.
[0013] Preferably, the surface modification is performed by a jet modifier, and the temperature for surface modification of silicon micropowders of different particle sizes is independently 100° C. to 140° C., and the time is independently 15 to 25 minutes.
[0014] Preferably, the particle size D 50 The mass of the silane coupling agent used for silicon micropowders of 2.5-3μm, 5-6μm and 9-10μm is 0.07-0.10%, 0.05-0.06% and 0.02-0.03% of the mass of silicon micropowders of corresponding particle sizes respectively.
[0015] Preferably, the mixing and compounding is carried out in a high-speed agitator, the inner lining and the rotor surface of the high-speed agitator are both made of zirconium oxide; and the mixing and compounding time is 3 to 5 minutes.
[0016] Preferably, the pore size of the sieve used for screening is 70 μm.
[0017] The present invention provides silicon dioxide fine powder for aluminum-based copper-clad laminates prepared by the preparation method described in the above technical solution.
[0018] The present invention provides application of the silicon dioxide fine powder for aluminum-based copper-clad laminates described in the above technical solution in aluminum-based copper-clad laminates.
[0019] The present invention ball-mills and grades quartz sand or coarse silicon micropowder to obtain silicon micropowder with different particle size distributions, performs surface modification on the silicon micropowder, and then compound the silicon micropowder with different particle size distributions to obtain silicon dioxide micropowder for aluminum-based copper-clad plates. Therefore, the silicon dioxide micropowder prepared by the present invention has the advantages of less magnetic impurities, high dimensional stability and high dispersibility.
[0020] The silicon dioxide micropowder for aluminum-based copper-clad laminate obtained by compounding and mixing coarse and fine particles in the present invention can effectively fill the gaps between coarse powder particles, and has the advantage of high filling amount. The silicon dioxide micropowder obtained by compounding and mixing coarse and fine particles is sieved through a sieve to make the CUT point (D 100) is controlled, effectively avoiding the existence of fatal large particles, and the particle size fully meets the use requirements of aluminum substrate fillers. Not only is the entire production process simple and safe, but the raw material cost is low. The silica powder can be used as a filler for aluminum-based copper-clad laminates, and has good overall performance.
[0021] The present invention uses a silane coupling agent to modify the surface of silicon dioxide powder, generates a grafting group on the surface of silicon powder, reduces the surface energy of silicon powder, effectively promotes the combination of silicon powder and insulating layer resin glue, cross-links to form a structure that is conducive to heat transfer, achieves the purpose of improving thermal conductivity, and simultaneously enhances interlayer adhesion, and improves peel strength and bending strength. The aluminum-based copper-clad plate processed by using the silicon dioxide micropowder as a filler has a certain improvement in peel strength, interlayer adhesion, bending strength, thermal conductivity and other properties compared with the performance of the plate produced by using similar silicon powder as a filler commonly found on the market. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The particle size distribution diagram of silicon powder for aluminum-based copper-clad laminate in Example 1;
[0023] Figure 2 The particle size distribution diagram of silicon powder in Comparative Example 1;
[0024] Figure 3 This is the particle size distribution diagram of the silicon powder in Comparative Example 2. DETAILED DESCRIPTION
[0025] The present invention provides a method for preparing silicon dioxide powder for aluminum-based copper-clad laminates, comprising the following steps:
[0026] The silicon-containing raw materials were ball-milled and classified in sequence to obtain particle sizes D 50 Silicon micropowders of different particle sizes are 2.5-3 μm, 5-6 μm and 9-10 μm respectively; the silicon-containing raw material is coarse silicon micropowder or quartz sand;
[0027] The silicon micropowders of different particle sizes are respectively mixed with silane coupling agents for surface modification, and the modified silicon micropowders of different particle sizes are mixed and compounded and then sieved to obtain silicon dioxide micropowder for aluminum-based copper-clad laminates;
[0028] The compounding mass ratio of the modified silicon micropowders with different particle sizes is (2.5-3 μm):(5-6 μm):(9-10 μm)=(10-15):(25-30):(50-60).
[0029] In the present invention, the parameters of the crude silicon powder or quartz sand are independently preferably whiteness ≥ 90%, more preferably 92%, magnetic impurity content ≤ 20 ppm, more preferably 15 ppm, purity ≥ 99.2%, more preferably 99.3%.
[0030] The quartz sand or coarse silicon powder used in the present invention is preferably subjected to magnetic separation and color separation to meet the above parameter requirements; the present invention has no special limitation on the magnetic separation and color separation, and can be carried out according to the process well known in the art.
[0031] The present invention has no particular limitation on the particle size of the quartz sand or coarse silicon powder, and quartz sand and coarse silicon powder well known to those skilled in the art can be used.
[0032] In the present invention, the ball mill lining and grinding media used in the ball mill are preferably made of alumina ceramic material; the present invention has no special limitation on the specifications of the ball mill used in the ball mill, and any ball mill known in the art can be used; in an embodiment of the present invention, the specifications of the ball mill are specifically 2.4m(Φ)*7.2m(L).
[0033] In the present invention, the interior of the classifier and the surface of the classifying wheel used for the classification are sprayed with an aluminum oxide coating to avoid the introduction of magnetic impurities. The frequencies of the classifier used for the classification are preferably 65Hz, 52Hz and 32Hz respectively; in an embodiment of the present invention, the classifying wheel of the classifier is a 6-wheel group, and the size of the classifying wheel is 315mm (Φ).
[0034] The present invention has no particular limitation on the specific process of the classification, and the particle size D is obtained by classification according to the process well known in the art. 50 Silicon powders with different particle sizes of 2.5 to 3 μm, 5 to 6 μm and 9 to 10 μm may be used.
[0035] In the present invention, the silane coupling agent preferably includes one or more of epoxyalkyl alkoxysilane, aminoalkoxysilane and isocyanate alkoxysilane; the epoxyalkyl alkoxysilane is preferably 3-(2,3-epoxypropoxy)propyltrimethoxysilane, the aminoalkoxysilane is preferably 3-aminopropyltrimethoxysilane; the isocyanate alkoxysilane is preferably 3-isocyanatepropyltrimethoxysilane.
[0036] In the present invention, the surface modification is carried out by a jet modifier, and the temperature for surface modification of silicon micropowders of different particle sizes is independently preferably 100°C to 140°C, more preferably 120°C to 130°C, and further preferably 123°C to 125°C, and the modification time is independently preferably 15 to 25 min, more preferably 18 to 23 min, and further preferably 20 min.
[0037] The present invention has no special limitation on the specifications of the jet-type modifying machine, and any corresponding jet-type modifying machine known in the art can be used.
[0038] In the present invention, the particle size D 50The mass of the silane coupling agent used for the silicon micropowders of 2.5-3 μm, 5-6 μm and 9-10 μm is 0.07-0.10%, 0.05-0.06% and 0.02-0.03% of the mass of the silicon micropowders of the corresponding particle sizes, respectively. 50 The mass of the silane coupling agent used for the silicon micropowder with a particle size of 2.5 to 3 μm is more preferably 0.08 to 0.09% of the mass of the silicon micropowder with the corresponding particle size, and more preferably 0.085%. 50 The mass of the silane coupling agent used for the silicon micropowder with a particle size of 5 to 6 μm is more preferably 0.055% of the mass of the silicon micropowder with the corresponding particle size; 50 The mass of the silane coupling agent used for the silicon micropowder with a particle size of 9 to 10 μm is more preferably 0.025% of the mass of the silicon micropowder with the corresponding particle size.
[0039] In the present invention, the composite mass ratio of the modified silicon micropowders with different particle sizes is (2.5-3 μm): (5-6 μm): (9-10 μm) = (10-15): (25-30): (50-60), preferably (10-13): (25-28): (56-60), and more preferably 10:25:60. The composite mass ratio of the modified silicon micropowders with different particle sizes, i.e., the particle size D 50 The compounding mass ratios of silicon micropowders are 2.5-3 μm, 5-6 μm, and 9-10 μm, respectively.
[0040] In the present invention, the mixing and compounding is carried out in a high-speed agitator, and the material of the inner lining and the rotor surface of the high-speed agitator is preferably zirconium oxide; the mixing and compounding time is preferably 3 to 5 minutes. The present invention has no special restrictions on the specifications of the high-speed agitator, and any high-speed agitator known in the art can be used.
[0041] In the present invention, the aperture of the sieve used for sieving is preferably 70 μm. In the present invention, large particles are removed by sieving.
[0042] The present invention provides silicon dioxide fine powder for aluminum-based copper-clad laminates prepared by the preparation method described in the above technical solution.
[0043] The present invention provides application of the silicon dioxide fine powder for aluminum-based copper-clad laminates described in the above technical solution in aluminum-based copper-clad laminates.
[0044] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0045] In the following embodiments, the specifications of the ball mill are specifically 2.4m (Φ) * 7.2m (L). The lining and grinding medium of the ball mill are both made of alumina ceramic materials; the interior of the classifier and the surface of the classifying wheel are sprayed with alumina coating, the classifying wheel of the classifier is a 6-wheel group, and the size of the classifying wheel is 315mm (Φ); when the mixed and compounded silicon micropowder is screened, the sieve aperture is 70μm.
[0046] Example 1
[0047] The quartz sand that has been color-sorted and magnetically-sorted is used as the raw material (whiteness 92%, magnetic impurity content 15ppm, purity 99.3%). The raw material is ground by a ball mill and then graded by a classifier. The classifier frequency is adjusted to 65Hz, 52Hz, and 32Hz respectively to obtain 2.5-3μm (D 50 )、5~6μm(D 50 )、9~10μm(D 50 ) of silicon powder;
[0048] Silica powder with particle sizes of 2.5-3μm, 5-6μm, and 9-10μm were surface-modified with 0.085%, 0.055%, and 0.025% of 3-(2,3-epoxypropoxy)propyltrimethoxysilane in a jet modifier at 125°C for 20 minutes, and the surface-modified silica powder was mixed and compounded in a high-speed stirrer according to a mass ratio of (2.5-3μm):(5-6μm):(9-10μm)=10:25:60. After stirring for 3 minutes, the mixed and compounded silica powder was sieved through a sieve to obtain silica powder for aluminum-based copper clad laminates.
[0049] Example 2
[0050] According to Example 1, 2.5-3 μm (D 50 )、5~6μm(D 50 )、9~10μm(D 50 ) of silicon powder;
[0051] Silica powders of 2.5-3 μm, 5-6 μm and 9-10 μm were surface-modified with 0.07%, 0.05% and 0.02% 3-aminopropyltrimethoxysilane in a jet modifier at 100°C for 23 minutes, and the surface-modified silicon powders were mixed and compounded in a high-speed stirrer according to the mass ratio of (2.5-3 μm):(5-6 μm):(9-10 μm)=13:28:56. After stirring for 3 minutes, the mixed and compounded silicon powders were sieved through a sieve to obtain silicon powders for aluminum-based copper-clad laminates.
[0052] Example 3
[0053] According to Example 1, 2.5-3 μm (D 50)、5~6μm(D 50 )、9~10μm(D 50 ) of silicon powder;
[0054] D 50 Silica powders of 2.5-3 μm, 5-6 μm and 9-10 μm are surface-modified in a jet modifier at 140° C. for 18 min using 3-isocyanatepropyltrimethoxysilane accounting for 0.09%, 0.06% and 0.03% of the mass of the silica powder, respectively. The surface-modified silica powders are mixed and compounded in a high-speed stirrer at a mass ratio of (2.5-3 μm):(5-6 μm):(9-10 μm)=15:30:50. After stirring for 3 min, the mixed and compounded silica powders are sieved through a sieve to obtain silica powders for aluminum-based copper-clad laminates.
[0055] Figure 1 is a particle size distribution diagram of silicon powder for aluminum-based copper-clad laminate in Example 1; Figure 1 As shown in the figure, the particle size distribution of silicon micropowder for aluminum-based copper-clad laminates is multi-peaked, indicating that the compounding of silicon micropowders of different particle size levels is relatively uniform, and the average particle size is about 6μm. In addition, no particles larger than 70μm were detected after sieving, which prevented the influence of large particles on the adhesive layer.
[0056] The whiteness of the silicon micropowder for aluminum-based copper-clad laminates obtained in Examples 1 to 3 is 93.4%, 93.6%, and 94%, respectively; the content of magnetic substances is 17ppm, 17ppm, and 19ppm, respectively; and the purity is 99.1%, 99.2%, and 99.2%, respectively.
[0057] Comparative Example 1
[0058] Comparative Example 1 is commercially available silicon micropowder of Lianyungang Weisheng Silicon Materials Co., Ltd. Model SG-1005, whiteness 91%, magnetic material 23ppm, purity 99.1%, particle size distribution Figure 2 shown.
[0059] Comparative Example 2
[0060] Comparative Example 1 is commercially available silicon micropowder of Lianyungang Weisheng Silicon Materials Co., Ltd. Model SG-1006, whiteness 90%, magnetic material 22ppm, purity 99.0%; particle size distribution is as follows Figure 3 shown.
[0061] Performance Testing
[0062] The silicon powders of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 were used as fillers to process aluminum-based copper-clad laminates.
[0063] Use a scraper to scrape 120μm of copper clad laminate glue on one side of the 18μm copper foil, dry and cool to room temperature to obtain a semi-cured insulating layer, overlap the glue-coated copper foil with the degreased and oxidized 5052 type 0.51mm aluminum plate, and hot press for 3h and keep warm for 1h in a vacuum press at a pressure of 10MPa and a temperature of 200℃ to obtain an aluminum-based copper clad laminate.
[0064] The preparation formula of the copper clad laminate adhesive is as follows: by weight, 51 parts of epoxy resin, 16 parts of phenolic resin, 3 parts of nitrile rubber (viscosity 85 seconds), 1.2 parts of electronic grade dicyandiamide (curing agent), 0.6 parts of imidazole (catalyst), 65 parts of DMF (solvent), the above raw materials are added to a container and stirred to fully dissolve to obtain a solution. The silicon micropowder described in Examples 1 to 3 and Comparative Examples 1 to 2 is added to the solution and stirred to obtain a stable copper clad laminate adhesive.
[0065] In this experiment, the copper clad laminate adhesive was adjusted to the same viscosity ((300±5) mPa*S, tested by a rotational viscometer at 25°C) by adding silicon powder of Examples 1 to 3 and Comparative Examples 1 to 2 in different proportions (mass fraction of silicon powder in the copper clad laminate adhesive, see Table 1).
[0066] According to the standards HG / T 2619-2007 "Aluminum substrate for printing" and GB / T 31988-2015 "Aluminum-based copper-clad laminate for printed circuits", the aluminum substrates prepared with the silicon powder of Examples 1 to 3 and Comparative Examples 1 to 2 were tested for peel strength, interlayer adhesion, bending strength, thermal conductivity, expansion rate, Tg, Td, and minimum breakdown voltage parameters.
[0067] The performance test results are shown in Table 1:
[0068] Table 1 Performance parameters of aluminum-based copper-clad laminates prepared from silicon micropowder in Examples 1 to 3 and Comparative Examples 1 to 2
[0069]
[0070]
[0071] It can be seen from Table 1 that under the same test conditions, the aluminum-based copper-clad laminate processed by using the silica powder produced by the method provided by the present invention as a filler has a high proportion of silica powder added, which can reduce a certain cost. Compared with the performance of the plate produced by using similar silicon powder commonly used in the market as a filler, the peel strength, interlayer adhesion, bending strength, thermal conductivity, breakdown voltage and other data are all improved, and the expansion rate, Tg, Td data are not much different, indicating that the silica powder produced by the method provided by the present invention is very suitable as a filler for aluminum substrates and should be promoted for use.
[0072] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing silicon dioxide powder for aluminum-based copper-clad laminates, characterized in that: The following steps are involved: The silicon-containing raw materials were ball-milled and classified in sequence to obtain particle sizes D 50 Silicon micropowders of different particle sizes are 2.5-3 μm, 5-6 μm and 9-10 μm respectively; the silicon-containing raw material is coarse silicon micropowder or quartz sand; The silicon micropowders of different particle sizes are respectively mixed with silane coupling agents for surface modification, and the modified silicon micropowders of different particle sizes are mixed and compounded and then sieved to obtain silicon dioxide micropowder for aluminum-based copper-clad laminates; The compounding mass ratio of the modified silicon micropowders with different particle sizes is (2.5-3 μm):(5-6 μm):(9-10 μm)=(10-15):(25-30):(50-60).
2. The method for preparing silicon dioxide powder for aluminum-based copper-clad laminate according to claim 1, characterized in that: The parameters of the crude silicon micropowder or quartz sand are independently whiteness ≥ 90%, magnetic impurity content ≤ 20 ppm, and purity ≥ 99.2%.
3. The method for preparing silicon dioxide powder for aluminum-based copper-clad laminate according to claim 1, characterized in that: The silane coupling agent includes one or more of epoxyalkoxysilane, aminoalkoxysilane and isocyanatealkoxysilane.
4. The method for preparing silicon dioxide powder for aluminum-based copper-clad laminate according to claim 3, characterized in that: The epoxyalkyl alkoxysilane is 3-(2,3-epoxypropoxy)propyltrimethoxysilane, the aminoalkoxysilane is 3-aminopropyltrimethoxysilane; and the isocyanate alkoxysilane is 3-isocyanatepropyltrimethoxysilane.
5. The method for preparing silicon dioxide powder for aluminum-based copper-clad laminate according to claim 1, characterized in that: The surface modification is carried out by a jet modifier, and the temperature for surface modification of silicon micropowders with different particle sizes is independently 100° C. to 140° C., and the time is independently 15 to 25 minutes.
6. The method for preparing silicon dioxide powder for aluminum-based copper-clad laminate according to claim 3, 4 or 5, characterized in that: Particle size D 50 The mass of the silane coupling agent used for silicon micropowders of 2.5-3μm, 5-6μm and 9-10μm is 0.07-0.10%, 0.05-0.06% and 0.02-0.03% of the mass of silicon micropowders of corresponding particle sizes respectively.
7. The method for preparing silicon dioxide powder for aluminum-based copper-clad laminate according to claim 1, characterized in that: The mixing and compounding is carried out in a high-speed agitator, the inner lining and the rotor surface of the high-speed agitator are both made of zirconium oxide; the mixing and compounding time is 3 to 5 minutes.
8. The method for preparing silicon dioxide powder for aluminum-based copper-clad laminate according to claim 1, characterized in that: The pore size of the sieve used for the sieving is 70 μm.
9. Silica powder for aluminum-based copper-clad laminates prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the silicon dioxide powder for aluminum-based copper-clad laminates according to claim 9 in aluminum-based copper-clad laminates.